2013
DOI: 10.1177/2158244013485581
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Key Visual Characteristics of Urban Plazas and Aesthetic Response

Abstract: Urban plazas as public spaces occur in every town and city around the world; however, some plazas are more user-friendly and successful than others. This study examined that “aesthetics” also have a significant impact to determine the extent of success of urban plazas and urban open spaces in combination with other quantitative factors, such as centrality of location, provision of services, and amenities. In addition, this research sought to focus on the relationship between visual characteristics and aestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Especially in the field of automotive design, Coughlan and Mashman (1999) suggested that design evaluation protocols that rely on a one-time evaluation may provide misleading information to designers and design decision-makers about consumer enthusiasm for a given design over its production lifetime. In recent years, the focus of relevant research has gradually shifted to exploring how to improve the scheme in the design process based on its performance evaluation (Cheshmehzangi, 2016;Lin & Twu, Creates a half-covered district with a combination of virtuality and reality and a transparent space, of which the designed structure is not only light and transparent but also solid and stable to construct a good sense of enclosure Ferdous (2013), and Özgüner and Kendle (2006) Water feature (E 2 )…”
Section: Performance Evaluation Methods Of Design Schemes In Relevant...mentioning
confidence: 99%
“…Especially in the field of automotive design, Coughlan and Mashman (1999) suggested that design evaluation protocols that rely on a one-time evaluation may provide misleading information to designers and design decision-makers about consumer enthusiasm for a given design over its production lifetime. In recent years, the focus of relevant research has gradually shifted to exploring how to improve the scheme in the design process based on its performance evaluation (Cheshmehzangi, 2016;Lin & Twu, Creates a half-covered district with a combination of virtuality and reality and a transparent space, of which the designed structure is not only light and transparent but also solid and stable to construct a good sense of enclosure Ferdous (2013), and Özgüner and Kendle (2006) Water feature (E 2 )…”
Section: Performance Evaluation Methods Of Design Schemes In Relevant...mentioning
confidence: 99%
“…The experts' views also are very important in the built environment based on their engagement of logical reasoning as a result of prior architectural training (Arifin&Sitorus, 2019).A correlation of both the users' and experts' evaluations can result in an objective position for an overall understanding and implementation of building façade design and construction practice. Relationship studies between experts and users' perception exists for different building typologies in Visual Quality Assessment (Arifin & Sitorus, 2019;Liu & Chuang, 2014;Ferdous, 2013;Ghomeshi, Nikpour, & Jusan, 2012). For instance, Safarova, Pirko, Jurík, Pavlica, and Nemeth (2019) engaged students and young architects in the investigation of their aesthetic opinion on residential building facades visual quality judgements.…”
Section: Introductionmentioning
confidence: 99%
“…Gungor and Polat (2018) in a landscape visual quality study also adopted the psychophysical approach by engaging a group of 115 experts in selecting the photographs for the study, while 230 students were involved in the main study. Ferdous (2013) with a similar approach also engaged experts and other respondents in a study of the connection between urban plazas aesthetic response and visual characteristics. In the light of these studies, it is clear to see that researchers have focused on experts and users independently; those with comparative study were on different building types; and different study location.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, F. Ferdous (Ferdous, 2013), J. Krase and T. Shortell (Krase, Shortell, 2011) studied public spaces of various global cities. S. Angel, J.…”
Section: Introductionmentioning
confidence: 99%